WATER RESISTANCE OF PLYWOOD BONDED WITH ALCOHOL-SOLUBLE PHENOL-FORMALDEHYDE RESIN - Jakimovska Popovska, Violeta; Iliev, Borche; Mihaylova, Julia (Innovation in Woodworking Industry and Engineering design, 2014)
Тhe aim of the research presented in this paper is to study the water resistance of experi-mental plywood bonded with alcohol-soluble phenol-formaldehyde resin. The evaluation of water resistance is made on the basis of the obtained data for the changes of the physical prop-erties of plywood after exposure to prolonged water treatment. Tests for the thickness swelling, volume swelling and water absorption are made after immersion in water for prolonged period in controlled laboratory conditions. The measuring of thickness, length, width and mass of ply-wood specimens for determination of these properties is made after immersion in water for the period of 1 day (24 hours) to 52 days (1248 hours).The experimental plywood model was made from peeled beech veneers. Pure alcohol-sol-uble phenol-formaldehyde resin is used as plywood binder.The research results showed that the plywood model has uniform density; it is dimension-ally stable during and after prolonged water treatment, without any deformations of the shape of the test specimens. The changes of the values of thickness and volume swelling, as well as the values of water absorption in the analyzed period are proportional to change of the duration of the period of water treatment. According to the obtained data from the tests of these proper-ties the plywood model meets the requirements of the standard for load-bearing plywood for use in construction.